Ergonomics : foundational principles, applications, and technologies. - McCauley Bush, Pamela, ....- (Boca Raton : CRC, 2012)
Inhoudsopgave : Foundational ErgonomicsSystems of the Human BodySenses of the Human Body and Measurement of Environmental FactorsMuscular Work and Nervous Control of MovementsAnthropometryDesign of Workplaces and Hand ToolsWork-Related Musculoskeletal DisordersHeavy Work and Evaluating Physical Workloads and LiftingInformation Ergonomics, Controls, and DisplaysWarning Labels, Instructions, and Product Liability